Answer:
![\therefore ((k+3))/((4k-2)).(12k^2+2k-4)=3k^2+11k+6](https://img.qammunity.org/2021/formulas/mathematics/high-school/xfbjnc5zd2zkqk4hlvjcr0x2kfdd42uh6q.png)
Explanation:
Factorization of a Quadratic polynomial:
- In order to factorize
we have to find out the numbers p and q such that, p+q = b and pq=ac.
- Finding the two integers p and q, we rewrite the middle term of the quadratic as px+qx. Then by grouping of the terms we can get desired factors.
Multiplication of two binomial:
(a+b)(c+d)
=a(c+d)+b(c+d)
=(ac+ad)+(bc+bd)
=ac+ad+bc+bd
Given that,
![((k+3))/((4k-2)).(12k^2+2k-4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/x9bbutkhigdoqk1nnsvnxl4xm70w9e83s3.png)
[ taking common 2]
[ cancel 2]
![=((k+3))/((2k-1)).(6k^2+4k-3k-2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/nsrlx7f3bywkp1pekguoslqoij7h1tt7v9.png)
![=((k+3))/((2k-1)).\{2k(3k+2)-1(3k+2)\}](https://img.qammunity.org/2021/formulas/mathematics/high-school/l2lkretzhnc8ckv58peujo9pin3vob970q.png)
![=((k+3))/((2k-1)).(3k+2)(2k-1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/7j9si7dalfpxxhdj27whfuy1d9kzl31f7k.png)
![=(k+3).(3k+2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/6bz3vacjanjw2yfty7h3y7xaj47ogg672k.png)
![=3k^2+9k+2k+6](https://img.qammunity.org/2021/formulas/mathematics/high-school/tu4m920vzz7dl2w9p8tye1cer1jsyvbhmk.png)
![=3k^2+11k+6](https://img.qammunity.org/2021/formulas/mathematics/high-school/zclwdhxm6uo53kazl9aw8libh4m9lcr1bq.png)
![\therefore ((k+3))/((4k-2)).(12k^2+2k-4)=3k^2+11k+6](https://img.qammunity.org/2021/formulas/mathematics/high-school/xfbjnc5zd2zkqk4hlvjcr0x2kfdd42uh6q.png)